Intermediaries for the greater good: How entrepreneurial support organizations can embed constrained sustainable development startups in entrepreneurial ecosystems - van Rijnsoever, Frank J. (Research Policy, 2022)
Sustainable development startups (SDSs) are important to help overcome societal challenges. However, starting an SDS or investing in them is a high-risk endeavor. Hence, policymakers are trying to make entrepreneurial ecosystems (EEs) more favorable for SDSs. A critical component of any EE is a financial support network, through which startups receive investments and business knowledge most importantly from private venture capitalists (VCs), among other finance providers. To be successful, SDSs thus need to become embedded in the financial support network. This embeddedness also allows SDSs to serve as network brokers between VCs and other startups, which is beneficial for the entire EE. Entrepreneurial support organizations (ESOs) can help build a sufficiently dense financial support network by introducing startups to other actors. However, there are often not enough promising SDSs in an EE to meaningfully influence the financial support network. This places ESOs that promote SDSs in the dilemma of which startups to admit: they can either focus their efforts exclusively on SDSs or give their unfilled spots to non-SDSs, with the latter facilitating network brokering among startups. Therefore, this paper answers the following research question: What is the effect from ESOs’ support mechanisms and admission regimes on the number of investments in SDSs? Using an agent-based model, I demonstrate that ESOs are a necessity for EEs with many constrained SDSs, particularly when the constraints are technology-based. Without ESOs, the presence of such SDSs negatively influences the entire EE due to a loss of brokering in the financial support network. ESOs can help repair this damage by having the right admission regimes and helping tenant SDSs overcome some of their constraints. Ultimately, the most effective way to do this is to have an admission regime under which only SDSs are accepted and receive twice as much support from the ESO.